Placement Analysis of Employee Performance in Health Services at the Health Office of Fakfak Regency - Waromi, Agustina; Absofi, Salma; Rahanra, Hans (Budapest International Research and Critics University, 2022)
Human resources in organizations, both government and private or in companies, are one of the valuable assets for organizational development. It is said that because the human resources owned by the company will determine whether the company will develop or experience setbacks. Therefore, it is necessary to manage human resources in order to be empowered optimally. The research method is qualitative. The results showed that the number of health centers in Fakfak Regency until the end of 2014 was 10 units, with details of the number of health centers being 7 units of care and 3 units of non-maintenance health centers. Until 2014 of the two new Puskesmas built, only one new puskesmas in Kampung Tomage is in the process of preparation for registration, as an effort to answer the needs and demands of the community which continues to increase for services and population growth. Conclusion Agencies are expected to apply a competency standard in employee placement, where the competency standard includes basic competencies and field competencies possessed by an employee.